Jobs in Iraq : A Primer on Job Creation in the Short-Term - Bandiera, Luca; Chandra, Vandana; Fosque, Jasmine; von der Goltz, Jan; Peterburs, Teresa Maria; Piffaretti, Nadia; Saba, Joseph; Wheeler, Collette (World Bank, Washington, DC, 2019)
Iraq needs a strategy to make rapid progress in tackling its profound jobs challenges. Iraq is facing a jobs crisis of unprecedented proportions. It could foment a resurgence in violence unless the Government of Iraq makes credible and swift progress in job creation and reconstruction. To shape a longer-term vision, Iraq can look beyond its recent history of conflict, and to its past as a diversified economy & home of an educated workforce. However, in the short-term, neither private/ public sector hiring can create jobs at the desired scale without significant new policy action. The first-best solution for large-scale private sector job creation hinges on structural reforms that must begin now, but are achievable only in the medium to longer term. This paper provides a primer on options to deliver large-scale job creation in the short term, based on investments in construction, agriculture and agribusiness, small & medium enterprises, and vocational skills. Its aim is to outline workable steps for progress in a jobs crisis in a post-conflict situation. Because these steps focus on rapid impact at scale, rather than structural reform, they are less-than-ideal or second-best. A similar logic applies to financing options. Financing needs for jobs are large, and while business climate reforms are under way, first-best private investment in jobs will remain limited. Yet, the recent oil price hike offers the Government of Iraq a uniquely timely opportunity to make an investment in jobs.